2000
DOI: 10.1097/00002800-200011000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Consultation in a Nursing Home

Abstract: As the world's population ages, increasing numbers of people can anticipate spending their latter years in long-term care settings. Many of these nursing home residents will also present psychiatric illnesses as primary or secondary diagnoses. The resulting behavioral problems may present challenges to nursing staff that they are ill-prepared to meet. This article illustrates the application of the Blake and Mouton consultation model to a Veterans Administration (VA) nursing home situation by a team of psychia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…[16][17][18][19][20][21][22][23][24][25][26][27][28] Psychiatric mental health CNSs use advanced knowledge about psychiatric disorders and psychotherapeutic modalities to manage care of persons with a wide range of psychiatric and mental health problems, including depression, 29-42 psychiatric emergencies, [43][44][45][46] addictive disorders, [47][48][49][50][51][52] and mental health problems related to medical illness. [53][54][55][56][57][58][59][60][61][62] As expert direct care providers, CNSs provide an indepth specialized assessment; this includes gathering information from a variety of sources, interpreting results from laboratory and diagnostic testing, and examining the multiplicity of patterns that evolve from the interplay of an array of biopsychosocial factors. 20,45,[63][64][65][66][67][68][69][70][71][72]…”
Section: First Substantive Area: Manage the Care Of Complex And/or Vumentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19][20][21][22][23][24][25][26][27][28] Psychiatric mental health CNSs use advanced knowledge about psychiatric disorders and psychotherapeutic modalities to manage care of persons with a wide range of psychiatric and mental health problems, including depression, 29-42 psychiatric emergencies, [43][44][45][46] addictive disorders, [47][48][49][50][51][52] and mental health problems related to medical illness. [53][54][55][56][57][58][59][60][61][62] As expert direct care providers, CNSs provide an indepth specialized assessment; this includes gathering information from a variety of sources, interpreting results from laboratory and diagnostic testing, and examining the multiplicity of patterns that evolve from the interplay of an array of biopsychosocial factors. 20,45,[63][64][65][66][67][68][69][70][71][72]…”
Section: First Substantive Area: Manage the Care Of Complex And/or Vumentioning
confidence: 99%
“…[226][227][228][229][230][231][232][233][234][235][236] Case consultation is described often by CNSs as a way to bridge the gap between knowledge and practice and thereby promote the clinical expertise of staff in meeting patients' and families' needs. 52,[56][57][58][59][60][61][62][237][238][239][240][241][242][243][244][245][246][247][248][249][250][251] The expertise of the CNS is maximized, and the staff members are assisted in acquiring new perspectives and approaches to problem solving, which are then generalized to a variety of patient care situations such as caring for patients with complex wounds, 245,249 disruptive behaviors, 57 persistent pain, 239 and mental health difficulties. [56][57][58][59][60][61][62]243,250,...…”
Section: Second Substantive Area: Educate and Support Interdisciplinamentioning
confidence: 99%
“…The motive for choosing psychiatric and geriatric health care professionals was that studies have shown that there are specific demands related to psychiatric care, for example, the intense interpersonal involvement with patients (Cronin-Stubbs & Brophy, 1985), dealing with violent incidents, and potential suicide of patients (Sullivan, 1993). The specific demands in providing health care to the elderly are found to be a lack of knowledge about how to provide the care (Cohen-Mansfield & Noelker, 2000;Kennedy, Covington, Evans, & Williams, 2000), insufficient preparation to meet emotional needs of patients (Kennedy, 2005), staffing (Bowers, Lauring, & Jacobson, 2001), heavy workload (Jerrard, 2003), and caring for patients suffering from agitation or dementia (Cohen-Mansfield & Noelker, 2000). After each interview was completed, the researcher asked the interviewee if someone closely connected to her could be asked to participate in the present study.…”
Section: Settings and Participantsmentioning
confidence: 99%
“…Similarly, EverCare APNs spent time coaching and teaching nursing home staff, communicating with families, and coordinating care (Abdallah, Fawcett, Kane, Dick, & Chen, 2005). APN geropsychiatric indirect care included mental health consultation-liaison services whereby APNs trained nursing home staff and administrators on mental health needs of residents, provided case consultation to staff, and supported nursing staff who were learning to incorporate geropsychiatric and mental health principles into usual care (Kennedy, Covington, Evans, & Williams, 2000;Smith, Mitchell, Buckwalter, & garand, 1995).…”
Section: Outcomes Of Apn Indirect Carementioning
confidence: 99%